Statutory Construction in Federal Appellate Tax Cases: The Effect of Judges' Social Backgrounds and of Other Aspects of Litigation - Daniel M. Schneider (Washington University Journal of Law & Policy, 2003)
The body of empirical legal research about how judges decide cases continues to expand, adding to the political science literature on the topic. Specifically, much has been written about how judges should interpret the Internal Revenue Code. However, the empirical research has failed to infuse the literature with observations about how judges presently interpret the Code. Indeed, lawyers have provided little empirical work addressing statutory interpretation. Yet different judges theoretically could justify the same result in a particular case either summarily, through reliance on precedent, or by deferral to the Internal Revenue Service. In fact, they actually do justify results for similar cases in different fashions. What leads judges down these different paths? Unlike the other literature addressing the Code’s interpretation, this Essay examines precisely that question.
Keywords: Law -- Interpretation & construction; Social science research; Federal judges; Sociological jurisprudence; Taxation